Respiration of Russian soils: Climatic drivers and response to climate change - Mukhortova, Liudmila; Schepaschenko, Dmitry; Moltchanova, Elena; Shvidenko, Anatoly; Khabarov, Nikolay; See, Linda (The Science of the total environment, 2021)
Soil respiration is one of the major ecosystem carbon fluxes and has a strong relationship with climate. We quantified this dependence for the Russian territory based on coupling climate data and in-situ soil respiration (Rs) measurements compiled into a database from the literature using regression and random forest models. The analysis showed that soil properties are a strong factor that mediates the climate effect on Rs. The vegetation class determines the contribution of the autotrophic respiration to the total Rs flux. The heterotrophic soil respiration efflux of Russia was estimated to be 3.2 Pg C yr−1 or 190 g C m−2 yr−1, which is 9–20% higher than most previously reported estimates. According to our modeling, heterotrophic soil respiration is expected to rise by 12% on average by 2050 according to the RCP2.6 climate scenario and at 10% based on RCP6. The total for Russia may reach 3.5 Pg C yr−1 by 2050. By the end of the century heterotrophic respiration may reach 3.6 Pg C yr−1 (+13%) and 4.3 Pg C yr−1 (+34%) based on RCP2.6 and RCP6, respectively. In order to understand to what extent the lack of information on disturbances impact contributes to uncertainty of our model, we analyzed a few available publications and expert estimates. Taking into account the specifics of Russian forest management and regional disturbance regimes, we have found that for the entire territory of Russia, the disturbances are responsible for an increase in heterotrophic soil respiration by less than 2%. [Display omitted] •Regression and random forest models of soil respiration were developed.•The soil type shapes the soil respiration response to the climate.•The average heterotrophic soil respiration was estimated to be 190±0.3 g C m–2 yr–1•Maps of current and future projected heterotrophic soil respiration are provided.